Influence of source and amount of dietary protein on the performance and reproductive function of first-calf heifers - W.C. Rusche; R.C. Cochran; L.R. Corah; Jeffrey S. Stevenson; D.L. Harmon (Kansas Agricultural Experiment Station Research Reports, 1992)
Increasing the amount of dietary protein above the NRC requirement increased weight gain of nursing first-calf heifers. Feeding a protein source with higher ruminal escape potential and increasing protein in the diet both improved calf gains. No significant changes in reproductive function or milk production were observed from either source or amount of dietary protein.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Beef cows; Protein; Escape protein; Reproduction; Milk